249 Prognostic role of diagnostic criteria of acute myocardial infarction. (8th December 2021) - Armillotta, Matteo; Sansonetti, Angelo; Angeli, Francesco; Fabrizio, Michele; Stefanizzi, Andrea; Bergamaschi, Luca; Magnani, Ilenia; Donati, Francesco; Toniolo, Sebastiano; Paolisso, Pasquale; Foà, Alberto; Rinaldi, Andrea; et al.
Abstract: Aims: The term acute myocardial infarction (AMI) reflects cell death of cardiac myocytes caused by ischaemia. The Fourth Universal Definition of Myocardial Infarction (UDMI) defined AMI by a typical rise and fall in the level of biochemical markers of myocardial necrosis together with criteria of myocardial ischaemia. However, the prognostic role of each single diagnostic criteria has never been explored. To evaluate the prognostic role of the different diagnostic criteria of AMI according to the Fourth UDMI. Methods and results: We enrolled all consecutive patients with AMI admitted from 2016 to 2019. We used a combination of criteria, according to the current ESC guidelines, to meet the diagnosis, namely the detection of an increase and/or decrease of high-sensitivity cardiac troponin I, with at least one value above the 99th percentile of the upper reference limit and at least one of the following: symptoms of ischaemia; ECG changes (new ST-T changes or new left bundle branch block); development of pathological Q waves in the ECG; imaging evidence of new loss of viable myocardium or new regional wall motion abnormality, in our study evaluated by transthoracic echocardiogram. All-cause mortality and a composite endpoint of all-cause mortality, re-hospitalization for heart failure, and myocardial re-infarction were collected. The predictive value of diagnostic criteria alone and its association were evaluated using Kaplan–Meier survival curves and subsequent Cox-regression analysis to find independent predictors of adverse events. 2386 patients were evaluated. The median follow-up time was 23.3 ± 14.5 months. The total number of events was 703 (29.5%). Kaplan–Meier curves showed that major adverse cardiac events (MACEs) were statistically different depending on the diagnostic criteria of AMI at admission. Particularly, clinical criteria alone showed a better predictive value ( P  < 0.001) than other diagnostic AMI criteria. Multivariable Cox-regression model demonstrated that clinical criteria were the independent predictor of good prognosis in patients with AMI (HR = 0.43; 95% CI: 0.28–0.67; P  < 0.001). Conversely, the other diagnostic criteria (electrocardiographic and echocardiographic) and the combination of all diagnostic criteria were not independent prognostic factors of MACEs (HR = 1.1; 95% CI: 0.6–2.4, P  = 0.6; HR = 1.1; 95% CI: 0.7–1.9, P  = 0.6; HR = 0.9; 95% CI: 0.7–1.0, P  = 0.2, respectively). Conclusions: Our data suggest that the prognosis is considerably better among patients with a diagnosis of AMI if clinical criteria alone are present at admission. We also demonstrated that clinical criteria are a strong prognostic predictor of good outcomes in patients with AMI. We hypothesize that the absence of electrocardiographic and echocardiographic alterations could indirectly indicate a smaller infarct sizes that contribute to patients' outcome.